Integrated Treatment Technology of Storage-Mining Inclined Goaf under Expressway - Weixing Bao; Zhiwei Ma; Haibo Wang; Jianjun Ren; Yong Huang; Bangwei Liang (Advances in Civil Engineering)
An inclined goaf caused by storage mining is a serious risk to subgrades and pavements. In this paper, effective investigation and detection methods of goafs were discussed considering the project of the Urumqi East Ring Expressway crossing the existing goaf of Zhongxing no. 2 mine. Moreover, by theoretical analysis and a series of field comparative tests, reasonable grouting parameters and the treatment plan were obtained. By comparing the test results of the field and laboratory, the influence of groundwater on the effect of grouting was revealed to reduce the compressive strength of the consolidating objects of the slurry. The high-density resistivity method presented strong anti-interference ability and high accuracy in a depth range of less than 150 m in the investigation of the goaf. The results of the treatment showed that it is necessary to conduct research and analysis from multiple aspects to obtain the best treatment plan of a goaf and ensure the safety of a project.